ROLE OF MODERN INFORMATION COMMUNICATION TECHNOLOGIES IN FINANCIAL REPORTING - Ergasheva Nigora Abdigapparovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article focuses on the effective use of information communication technologies and its importance in the preparation of financial reports, as well as the possibilities of effective use of accounting software packages used in our country. Also, proposals are given on the effective use of modern information and communication technologies in the preparation of financial reports.